APPLYING THE THEORY OF CONSTRAINTS TO ENHANCE OPERATIONAL EFFICIENCY IN INDUSTRIAL MICRO AND SMALL ENTERPRISES: EVIDENCE FROM PIURA, PERU (Lex localis - Journal of Local Self-Government, 2025)
This study analyzes the impact of the Theory of Constraints (TOC) on operational efficiency among micro and small enterprises (MSEs) in the industrial sector of Piura, Peru. A quantitative methodology was applied through structured surveys administered to local enterprises to identify, evaluate, and improve the principal constraints affecting their processes, as well as to determine the benefits derived from TOC implementation. The findings indicate that most MSEs are emerging businesses characterized by reduced labor structures and empirical operational practices, where logistical bottlenecks—particularly in procurement, transportation, warehousing, and distribution—predominate alongside deficiencies in process standardization, technology, and quality management. The absence of standard operating times and the prevalence of informal procedures generate inefficiencies and diminish competitiveness. Corrective measures were designed following TOC’s five focusing steps, including supplier negotiation, supply diversification, route planning, adoption of modern warehouse management systems, technological upgrading, and the implementation of certified quality management frameworks. The results demonstrate that TOC substantially reduces operating times, optimizes resource utilization, and enhances customer satisfaction, thereby strengthening the profitability, sustainability, and competitiveness of MSEs in dynamic environments. Moreover, these improvements extend beyond operational performance to foster financial stability, job creation, and sustainable local development.